A Text Mining Analysis for Research Trend about the Mathematics Education - 진미르; 고호경 (East Asian Mathematical Journal, 2019)
In this paper we used text mining method to analyze journals of mathematics education posterior to the year of 2016. To figure out trends of mathematics education research. we analyzed the key words largely mentioned in the recent mathematics education journals by Term Frequency and Term Frequency-Inverse Document Frequency method. We also looked at how these keywords match up with the key words that appear of education to prepare for future society. This result can infer the characteristics of mathematics education research in the aspect upcoming research topics.
Keywords: research trend; mathematics education; keyword; text mining